A Comparative Policy for the COVID-19 Emergency Management of Frontline Health Workers in Selected African Countries - Mary S. Mangai; Tyanai Masiya; Yul Derek Davids (Indonesian Association for Public Administration, 2022)
Health workers are often exposed to health risks and danger in the discharge of their duties. This is especially distressing during the COVID-19 pandemic. This study employs a multiple case study design to investigate the COVID-19 emergency management of frontline workers in South Africa, Kenya, Ghana, and Nigeria. The findings from the study reveal that governments in the selected countries prioritize the response phase of the emergency management theory over the mitigation and preparedness phases. The response phase was meted with inevitable consequences. Health workers feared risking their lives, and the majority threatened to abandon their jobs due to insufficient personal protective equipment (PPE) and welfare support. The study concludes that the government should prioritize all the phases of emergency management instead of focusing on the response phase, which involves the use of both human and financial resources on an overwhelming pandemic. They should have prepared the frontline workers adequately and equipped their health systems in preparation for any impending epidemic.